On the poorly known haplogynae spiders of the genus Ochyrocera Simon (Araneae, Ochyroceratidae) from Mexico: description of two new species with an updated identification key for Mexican species - Valdez-Mondragón, Alejandro (Zootaxa, 2017)
Two new species of the spider genus Ochyrocera Simon 1891 are described from Mexico. Ochyrocera jarocha new species was collected under rotten trunks and hollow trunks in a tropical rainforest, in San Martin Volcano, Veracruz, Mexico. Ochyrocera pojoj new species was collected in a mixed forest, under rotten trunks, in La Trinitaria, Chiapas, Mexico, which represents the third species described from the state of Chiapas. With the description of the two new species herein, six species of Ochyrocera are recorded from Mexico. An updated taxonomic identification key and a distribution map to the Mexican species are provided.